Perbuatan Melanggar Hukum Dalam Perjanjian Kerjasama Pengelolaan Hotel: (Studi Putusan Nomor : 263/ Pdt. G/2014/ PN. Mtr) - Rifqi Khaeratul Ihsan; M. Yazid Fathoni (Fakultas Hukum Universitas Mataram, 2022)
This study is a normative one with statute, conceptual, and case approach. The study is conducted by analyzing issues-related cases that are settled already with permanent legal force. Sources and materials in this study are secondary ones, which are laws and regulations related to the case and issue, obtained through literature study. Results of this study identify indicators as judges’ consideration material in deciding the act of abusing the law, in particular, in the cooperation agreement of hotel management (A Study of Decision No : 263/ pdt. G/2014/ PN. Mtr).